Strategi Kepala Madrasah Dalam Mengelola Sumber Daya Manusia Untuk Mewujudkan Budaya Religius Di MA Nurul Hikmah Besuki Situbondo - Sri Widartik; Irzak Yuliardy Nugroho; Arifia Retna Yunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is based on the crucial role of madrasahs in developing religious character in the era of modernization and globalization, which often includes instilling an understanding of religious values ​​among students. Specifically, at MA Nurul Hikmah Besuki Situbondo, several crucial issues in human resource (HR) management were identified, including the unequal distribution of teaching assignments among teachers, minimal involvement in religious programs, and a decline in student motivation for religious routines after the pandemic. This phenomenon underscores the urgency of a strategic approach from madrasah leaders to optimize HR management to create a stronger and more sustainable religious culture. This study employed a qualitative approach with descriptive research. Data collection techniques included in-depth interviews, participant observation, and documentation.Observations revealed that the madrasah principal implemented human resource management strategies through a thorough and structured planning process. Examples include the development of comprehensive religious programs and efforts to improve teacher qualifications based on Islamic principles. During implementation, these strategies were realized through the establishment of religious-based routines, exemplary leadership, and the strengthening of organizational norms imbued with Islamic values. Meanwhile, the evaluation process is carried out routinely, integrating the level of teacher and student involvement, while also measuring its impact on the sustainable formation of religious character. This research reveals that achieving a strong religious culture is highly dependent on the visionary leadership approach of the madrasah principal in optimizing human resource management.